2009
DOI: 10.1253/circj.cj-08-1086
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Clinical Benefit of Improved Angiographic Results With Sirolimus-Eluting Stents Compared With Paclitaxel and Zotarolimus-Eluting Stents in Patients With Acute Myocardial Infarction Undergoing Percutaneous Coronary Intervention

Abstract: rug-eluting stents (DESs) have been rapidly accepted in real world clinical practice by the interventional community, largely being used in percutaneous coronary interventions (PCI). 1 Previous randomized trials have reported that the first generation DESs, including sirolimus-eluting stents (SES; Cypher™) and paclitaxel-eluting stents (PES; Taxus™) reduced the incidence of restenosis and the need for revascularization over 6-12 months' follow-up compared with bare metal stents (BMSs). 2,3 Recent trials of DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Korea Acute Myocardial Infarction Registry (KAMIR) study showed that the first-generation SES had the lower 1 year incidences of major adverse cardiac events (MACEs) and target lesion revascularization (TLR) than the second-generation ZES in patients with ST-segment elevation myocardial infarction undergoing primary PCI [9]. However, the benefit of the first-generation DES was not shown in an early small-scale study [10] and a randomized trial [11]. In contrast, the second-generation EES appeared to be associated with lower incidences of MACEs [12] and definite and/or probable stent thrombosis in patients with ST-segment elevation myocardial infarction [13].…”
Section: Introductionmentioning
confidence: 99%
“…Korea Acute Myocardial Infarction Registry (KAMIR) study showed that the first-generation SES had the lower 1 year incidences of major adverse cardiac events (MACEs) and target lesion revascularization (TLR) than the second-generation ZES in patients with ST-segment elevation myocardial infarction undergoing primary PCI [9]. However, the benefit of the first-generation DES was not shown in an early small-scale study [10] and a randomized trial [11]. In contrast, the second-generation EES appeared to be associated with lower incidences of MACEs [12] and definite and/or probable stent thrombosis in patients with ST-segment elevation myocardial infarction [13].…”
Section: Introductionmentioning
confidence: 99%
“…19 In the Massachusetts registry, the largest and the longest data to date, the incidence of ST was not presented. 20 Korean multicenter registry data also showed similar rates of ST. 22, 23 The ST data warrant a couple of discussion points. First, our data again shows the high rates of ST in the AMI setting, a factor which has been shown to be an independent predictor of ST after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, among first generation DES, important differences can be found, generally in favor of sirolimus, 57-61 and also new generation DES performed better than older ones. 62, 63 Unfortunately, no stent type subgroup analysis was possible, as most of the collected papers do not report endpoints according to the type of DES implanted. However, if only sirolimus or new generation DES were used instead of paclitaxel DES, the good results observed in the DES population could probably be reinforced.…”
Section: Study Limitationsmentioning
confidence: 99%